Intracellular Complement Component 3 Attenuated Ischemia-Reperfusion Injury in the Isolated Buffer-Perfused Mouse Heart and Is Associated With Improved Metabolic Homeostasis - Torp, M-K.; Ranheim, T.; Schjalm, C.; Hjorth, M.; Heiestad, C.M.; Dalen, K. T.; Nilsson, P. H.; Mollnes, T. E.; Pischke, S. E.; Lien, E.; Vaage, J.; Yndestad, A.; et al. (Frontiers in Immunology, 2022)
The innate immune system is rapidly activated during myocardial infarction and blockade of extracellular complement system reduces infarct size. Intracellular complement, however, appears to be closely linked to metabolic pathways and its role in ischemia-reperfusion injury is unknown and may be different from complement activation in the circulation. The purpose of the present study was to investigate the role of intracellular complement in isolated, retrogradely buffer-perfused hearts and cardiac cells from adult male wild type mice (WT) and from adult male mice with knockout of complement component 3 (C3KO). Main findings: (i) Intracellular C3 protein was expressed in isolated cardiomyocytes and in whole hearts, (ii) after ischemia-reperfusion injury, C3KO hearts had larger infarct size (32 ± 9% in C3KO vs. 22 ± 7% in WT; p=0.008) and impaired post-ischemic relaxation compared to WT hearts, (iii) C3KO cardiomyocytes had lower basal oxidative respiration compared to WT cardiomyocytes, (iv) blocking mTOR decreased Akt phosphorylation in WT, but not in C3KO cardiomyocytes, (v) after ischemia, WT hearts had higher levels of ATP, but lower levels of both reduced and oxidized nicotinamide adenine dinucleotide (NADH and NAD+, respectively) compared to C3KO hearts. Conclusion: intracellular C3 protected the heart against ischemia-reperfusion injury, possibly due to its role in metabolic pathways important for energy production and cell survival.